Hubungan Konsumsi Makanan Dengan Status Gizi Anak Usia Sekolah SD 3 Muhammadiyah Palembang - Subhan Muhith (IKesT Muhammadiyah Palembang, 2024)
Food is a type of food that is very well known and commonly consumed by the public, including school children. Data (WHO) on the nutritional status of children in the world with a prevalence of emaciation of around 13.9%, obesity of >340 million people. Riskesdas in 2018 for children aged 5-12 years based on the BMI/U index with a thin nutritional status of 6.8% and an obesity nutritional status of 9.2%. Riskesdas for South Sumatra Province in 2018, the prevalence of nutritional status of children aged 5-12 years was based on the BMI/U index with the nutritional status of thin children at 6.26% and the nutritional status for obesity at 9.08%. Meanwhile, based on Palembang City data, the BMI/U index for the nutritional status of thin children is 6.88% and the nutritional status of obese children is 11.59%. Snacks that are not guaranteed to be clean can cause digestive disorders and poisoning. To determine the relationship between food consumption and the nutritional status of school-aged children. His research used a descriptive analytical design with a cross-sectional approach. The number of research respondents was 169 students. The research instrument used was a Semi Quantitative Form-FFQ questionnaire with interview and questionnaire methods taken at one time. The research carried out was located at SD 3 Muhammadiyah Palembang in March 2024. The variables explained included the characteristics of the respondents (age, parents' education, parents' occupation and nutritional status of the respondents). The research data used for statistical tests was the Spearman Correlation analysis test. Research Results: There is a relationship between food consumption and the nutritional status of school-aged children (p value 0.000 < 0.05). The higher the frequency of food consumption, the risk of obesity in school-aged children will increase. Keywords : School age children, Food consumption, Nutrional Status Bibliography : 11 (2020-2023).